Investigation of Nodal Numerical Adjoints From CMFD-Based Acceleration Methods - Oh, Taesuk; Kim, Yonghee (Frontiers in Energy Research, 2022)
In this work, the attribute of mathematical adjoints acquired in association with various coarse-mesh finite difference (CMFD) accelerated nodal methods based on the nodal expansion method (NEM) is studied. The direct transposition is implemented to the NEM-CMFD system matrix including correction factors for acquisition of adjoint flux. It is shown that the numerical adjoint functions vary significantly according to the type of CMFD acceleration method being utilized, e.g., CMFD, pCMFD, and one-node CMFD, where negative values can be encountered depending on the problem. With regards to the one-node CMFD acceleration, a mathematical description for encountering negative adjoint flux values is given alongside a remedy to stifle such an occurrence. A systematic assessment is conducted for adjoint flux acquired from each acceleration scheme based on the first-order perturbation theory, where erroneous reactivity estimation could occur due to negative adjoint flux values.